Outcomes of Onlay Versus Sublay Mesh Hernioplasty for Ventral Abdominal Hernias - Saleem, Saadan; Naqvi, Syeda Rifaat Qamar; Luqman, Aimen; Razzaque, Hasnain; Khan, Mahlail Hassan; Haq, Qazi Tafheem Ul (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare surgical outcomes of Onlay versus Sublay technique of mesh hernioplasty among patients with ventral abdominal hernia.Study Design: Quasi-experimental study.Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 to Mar 2022.Methodology: A total of 78 patients were selected, using convenience sampling, with reducible incisional, paraumbilical, supraumbilical or epigastric hernia, with a hernial defect measuring ≥2 cm. All preoperative parameters were recorded, and postoperative outcomes were monitored on follow-up at 2 weeks, 1 month and 2 months. Data was analyzed for statistical significance with p-value ≤0.05 being considered significant.Results: Open Onlay repair was performed on 41(52.6%) patients whereas the remaining 37(47.4%) cases had open Sublay mesh hernioplasty. The commonest ventral hernia types were paraumbilical 43(55.1%) and incisional 28(35.9%). Sublay procedure lasted for a significantly longer duration (p